Unilever's mission for vitality - Austen-Smith, David, (SAGE Knowledge. Cases., 2007)
This case walks students through the types of dilemmas that executives face in the real world. Dove and Axe are two highly successful brands owned by Unilever, a portfolio company (www.unilever.com). Dove is a female-oriented beauty product brand that exhorts "real beauty" and not the unachievable standards that the media portrays. In contrast, Axe is a brand that purportedly "gives men the edge in the mating game." Axe's risqu? commercials portray the supermodel-type beauty ideal that Dove is trying to change.Unilever had always been a company of brands, i.e., the consumer knew the brands but not the company. Recently, however, the company attempted to unify with an umbrella mission for all of its brands. This change would turn Unilever into a company with brands, potentially increasing consumer awareness and encouraging cross-purchases between the different brands. However, this new strategy raised questions about the conflicting messages between the brands' marketing campaigns, most notably between Unilever's two powerhouse brands, Dove and Axe.